The challenges of global bioethics. Issue 1 (31st December 2022) - ten Have, Henk
ABSTRACT: The Covid-19 pandemic is associated with an increase in ethics publications and an upsurge of interest in global bioethics. This commentary argues that global bioethics is broader than international bioethics, as defined by Macklin, because the nature of moral problems is determined by processes and practices of globalization, and because a broader theoretical perspective is required. Such perspective acknowledges the connectedness and relationality of human beings, as assumed in the care-based feminist bioethics defended by Tong. The commentary finally claims that a rights-based approach is not opposed to but reinforces a care-based global bioethics.